PRILAKU KONSUMEN DALAM MEMUTUSKAN PEMBELIAN PRODUK MAKANAN YANG MEMILIKI LABELISASI HALAL - Silvy Rahma; Muhammad Dzaky; Windy Della Sari (Akademi Pariwisata Bunda Padang, Sumatera Barat, Indonesia, 2023)
This research is a mini qualitative research, this research uses survey method, which is a study that takes samples from the population and collects data through questionnaires as a tool or is called descriptive research. This descriptive study aims to determine consumer behavior in deciding to purchase food products labeled halal. The population in this study is the public in purchasing food products labeled halal. Sampling in this study amounted to 105 respondents. In this study, consumer behavior in making decisions is seen from three factors, namely cultural factors, personal factors and social factors. Data collection was carried out using a Likert scale. The results showed that cultural factors that greatly influence consumers in making decisions in buying food products labeled halal as much as 60% agreed while social factors only showed 59% agreed and personal factors 34% agreed.